Application of uniform design experimental method in waste cooking oil (WCO) co-hydroprocessing parameter optimization and reaction route investigation. (15th December 2017) - Wang, Hui; Zhang, Lin; Li, Guoliang; Rogers, Kyle; Lin, Hongfei; Seers, Patrice; Ledan, Thomas; Ng, Siauw; Zheng, Ying
Abstract: A blend of waste cooking oil (WCO, 10–30 wt%) and dodecane was co-hydroprocessed over a supported CoMo sulfided (CoMoS) catalyst in a fixed bed reactor. Uniform design (UD) method, where small number of experimental points randomly distributed over an s-dimensional unit cube, was used for the first time to optimize WCO co-hydroprocessing parameters and to investigate the reaction routes. In only four trials, the reaction routes totally changed and high temperature at 365 °C was found to be the key factor to change the reaction route. The results of another three trials confirmed that temperature significantly affected the reaction routes and the liquid product distribution. Hydrogenation and deoxygenation were the dominant reactions at temperatures of 275–325 °C, whereas at a temperature of 365 °C, cracking and dehydrogenation reactions were the dominant reactions. In eight trials, a suitable operational window was established. 20% and 10% were found to be good blend ratios for WCO deoxygenation, and for both deoxygenation and hydrogenation within the optimum operational window. All the optimal conditions were proven to have good adaptability for camelina oil upgrading. Finally, engine tests conducted by blending the WCO based fuel above to diesel in equal proportion resulted into decrease of major pollutant emissions (CO, UHC, NO) when compared to conventional diesel.